(untitled) (Research, Society and Development, 2023)
Introduction: Endodontics is a specialty of dentistry dedicated to the study and treatment of diseases that affect the pulp tissue and acts in the treatment and prevention of lesions that affect the periradicular tissues. Nowadays, dentistry is becoming more and more sophisticated, making it less invasive, less painful and more effective with the use of complementary therapies, such as ozone therapy. A natural compound, it has high antimicrobial effects and is composed of three oxygen atoms, where each oxygen atom is linked to the others by a simple bond, through electrical discharges that break down and form O3, also called ozone. Objectives: The aim of this study is to present complementary therapies that help to reduce microorganisms, aiding healing and elimination during endodontic treatments, with the aim of improving patient care and recovery. Material and methods: This is an integrative review study with a qualitative approach, looking at ozone therapy in root canal treatment with complementary therapies. Discussion: Ozone stands out in dentistry because it is a minimally invasive method and has unique characteristics. Its application can be through gas, ionized water or associated with other substances, such as oils. Conclusion: Many studies have shown controversy regarding the use of ozone and its efficacy in endodontics, diverging from one another, demonstrating the need for more studies to establish a standardization of this therapy and its effects, thus making it necessary to create a specific protocol for this therapy.